2016
DOI: 10.1007/s00253-016-7991-9
|View full text |Cite
|
Sign up to set email alerts
|

Identification of alkaline phosphatase genes for utilizing a flame retardant, tris(2-chloroethyl) phosphate, in Sphingobium sp. strain TCM1

Abstract: Tris(2-chloroethyl) phosphate (TCEP) is a haloalkyl phosphate flame retardant and plasticizer that has been recognized as a global environmental contaminant. Sphingobium sp. strain TCM1 can utilize TCEP as a phosphorus source. To identify the phosphomonoesterase involved in TCEP utilization, we identified four putative alkaline phosphatase (APase) genes, named SbphoA, SbphoD1, SbphoD2, and SbphoX-II, in the genome sequence. Following expression of these genes in Escherichia coli, APase activity was confirmed f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 28 publications
0
18
0
3
Order By: Relevance
“…It is considered that a phosphotriesterase, PDE and PME are involved in the degradation of TCEP. While phosphoesterases catalyzing the first and third steps of TCEP degradation in TCM1 have been identified in our previous studies as a HAD 9 and an alkaline phosphatase 10 respectively, no information has been reported on a PDE from this microorganism. In the present study, Sb -PDE from Sphingobium sp.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…It is considered that a phosphotriesterase, PDE and PME are involved in the degradation of TCEP. While phosphoesterases catalyzing the first and third steps of TCEP degradation in TCM1 have been identified in our previous studies as a HAD 9 and an alkaline phosphatase 10 respectively, no information has been reported on a PDE from this microorganism. In the present study, Sb -PDE from Sphingobium sp.…”
Section: Discussionmentioning
confidence: 83%
“…However, it has already been reported that two alkaline phosphatases, SbPhoA and SbPhoX-II, are involved in the utilization of TCEP by Sphingobium sp. strain TCM1 and the double gene mutant did not grow on TCEP medium 10 . These results suggest that Sb -PDE catalyzes only the second step in the degradation of organophosphorus triesters, and not the third (phosphomonoester hydrolysis) step, although the PME activity of the enzyme toward monohaloalkyl phosphate was not determined in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The OPs used in our MIX treatment are proven to be degradable and hence can be used as a resource for bacteria (Leahy and Colwell, ; Takahashi et al ., , , , ; Seo et al ., ; Abe et al ., , ; Joye et al ., ; Kera et al ., ; Vila‐Costa et al ., )). Yet, our study showed notably negative effects on bacterial growth of hydrocarbons and OPEs supplied at environmentally relevant concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…strain TCM1. The successive cleavage of the phosphate ester bond is a common step in the biodegradation of OPFRs such as TCEP, TBP and TPP [15,29,36]. The biodegradation path of TCPP and its derivative molecule TCPP-OH was simulated in accordance with the biodegradation path of TBP, which led to the greatest improvement in biodegradation and photodegradation and deduction of microbial degradation products (Figure 3).…”
Section: Mechanistic Analysis For the Enhancement Of Biodegradation Fmentioning
confidence: 99%